Educational Cosmopolitanism and Intellectual Transmission in Andalusia Based on Contemporary Islamic Education - Bahri, Samsul (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of this research is regarding cosmopolitanism as an attitude of openness towards things that exist and come from outside which is very much needed in supporting the progress and development of education and science. Because it is almost certain that no single nation or society in this world is capable of developing its own knowledge base and technology. Among the causes of backwardness in a society is because society is inclusive, unwilling and not ready to accept ideas from other cultures and civilizations. This study uses a historical methodology approach with four steps: first, heuristics, namely the process of finding the necessary data sources. Heuristics are techniques or ways to find sources that can be obtained through literature studies, direct observations in the field (if possible and necessary); second, criticism of the source, namely the process of examining the source. whether the source found is genuine or fake. Source criticism consists of internal and external criticism; third, interpretation, which is an attempt to interpret by looking for relationships between the various facts found; fourth, historiography, namely the stage of writing history into historical stories or stories. The results of the study stated that the extraordinary achievements in science, education and civilization that had been achieved by Muslim communities, especially in Andalus, prompted the author to conduct research on the education and scholarly traditions of scholars in Andalusia. So that it is hoped that it will be able to reveal the secrets that made the Andalus people a society, where education, science, civilization and culture could develop brilliantly which outperformed education, science and civilization in all parts of the world at that time.